Are Australian Pharmacists Willing to Work in a Disaster?. Issue Volume 34:Issue s1(2019) (May 2019) - McCourt, Elizabeth; Watson, Kaitlyn; Singleton, Judith; Tippett, Vivienne; Nissen, Lisa
Abstract : Introduction: Current literature suggests that a large percentage of the health workforce may be unwilling to work during a disaster. The willingness of pharmacists to work during a disaster is under-researched internationally and non-existent in Australia. Aim: To determine if Australian pharmacists are willing to work in a disaster and the factors that affect the willingness to work. Methods: A 13-question survey was developed from the current literature and released nationally through professional organizations and social media. Results: Sixty Australian pharmacists completed the survey. Most participants believed their pharmacy was an essential service for their community. Pharmacists reported they would be likely to report to work during a pandemic or biological disaster (73%) or natural disaster (78%). The two major factors likely to prevent pharmacists from working in a disaster are family and safety concerns. Pharmacists perceived that their duty of care to their patients would make them likely to work during a disaster. Most pharmacists noted they would work even if they were expected to work outside their scope of practice, or if their place of work lacked electricity or was damaged. Discussion: Depending on the disaster, up to 27% of the pharmacy workforce may be unwilling to work in a disaster. Family and safety concerns were the primary barriers to pharmacists reporting to work in the aftermath of a disaster. Providing guidelines on how pharmacists can prepare their family for a disaster may assist in ensuring pharmacists are willing to work. The pharmacists surveyed demonstrated a strong commitment to their duty of care with the majority stating they would be likely to work in austere work environments. This research raises questions of the safety of pharmacists working outside their scope and in austere environments and whether it is safe for them, their patients, and the broader community.